An analysis of young-band repertoire in the context of culturally responsive teaching - Bennett, Hollie E., author; Johnson, Erik, advisor; Phillips, Rebecca, advisor; Coffino, Kara, committee member; Pippen, John, committee member (Colorado State University. Libraries, 2020)
Repertoire is a highly discussed topic especially for band music educators (Battisti, 2018; Brewer, 2018; Dziuk, 2018; Koch, 2019; Mantie & Tan, 2019). Many educators even view the "repertoire as the curriculum" (Reynolds, 2000, p. 31) making it a core tenet of the band music classroom. Repertoire can be chosen using a variety of filtering systems including alignment with music education philosophy (Allsup, 2018; Elliott, 1995; Jorgensen, 2003; Reimer, 1959; Reimer, 2009), artistic merit (McCrann, 2016; Ostling, 1978; Ormandy, 1966) and potential for musical learning (Apfelstadt, 2000; Hopkins, 2013). However, many critics of band repertoire claim that it is limiting to inclusive education purposes pertinent to contemporary music education classrooms (Abril, 2003; Elpus & Abril, 2011; Elpus & Abril, 2019; DeLorenzo, 2012; Kratus, 2007; Lind & McKoy, 2016; Soto, 2018). While repertoire is important when taking into consideration the development of comprehensive musical dispositions that are required for students to fully engage with music in their lived experience. Many music teachers may use repertoire alone to foster connections with student cultural referents (DeLorenzo, 2019; Shaw, 2020). However, inclusive instructional approaches such as Culturally Responsive Teaching (Gay, 2010; Hammond, 2015; Ladson-Billings, 2009; Lind & McKoy, 2016), Multicultural Education (Banks, 2015; Banks, 2019; Nieto, 2009), and Funds of Knowledge (Amanti, Moll, & González, 2005; Rios-Aguilar, 2010) can help to address the multitude of diverse student needs within the music classroom (DeLorenzo, 2019; Ravitch, 2010; Shaw, 2010). Guided by the tenets of inclusivity, teachers are also called upon to consider the importance of student cultural validation, background knowledge, as well as becoming increasingly aware of diverse repertoire and increasingly flexible with instruction when selecting repertoire (Abril, 2009; DeLorenzo, 2012; Shaw, 2020). The aim of this study is to provide a framework to help clarify the unique relationship between repertoire for young wind band and opportunities for responsive, student-centered instructional approaches.
Keywords: funds of knowledge; multicultural education; young band repertoire; inclusive music education; culturally responsive teaching; representation